Inhibition of MIR4435-2HG on Invasion, Migration, and EMT of Gastric Carcinoma Cells by Mediating MiR-138-5p/Sox4 Axis - Gao, Li-Fei; Li, Wei; Liu, Ya-Gang; Zhang, Cui; Gao, Wei-Na; Wang, Liang (Frontiers in Oncology, 2021)
Background: The previous investigations have identified that long non-coding RNA (LncRNAs) acts as crucial regulators in gastric carcinoma. However, the function of lncRNA MIR4435-2HG in the modulation of gastric carcinoma remains elusive. Here, we aimed to explore the role of MIR4435-2HG in gastric carcinoma. Method: TCGA and GEO were applied to select the differently expressed LncRNAs in gastric carcinoma. The qRT-PCR was applied to analyzed MIR4435-2HG expression in carcinoma tissues and cell lines. The effect of MIR4435-2HG on proliferation, invasion, migration, and apoptosis of gastric carcinoma cells was detected by CCK-8 assays, Transwell assays, and flow cytometry in vitro. A subcutaneous tumor model was constructed to examine the tumor growth of gastric carcinoma cells after knocking out MIR4435-2HG. RNA immunoprecipitation and luciferase reporting assays were applied to evaluate the interaction of MIR4435-2HG, miR-138-5p, and Sox4. Results: The bioinformatics analysis based on TCGA and GEO database indicated that MIR4435-2HG was obviously elevated in gastric carcinoma samples. The qRT-PCR analysis revealed that MIR4435-2HG was upregulated in clinical gastric carcinoma tissues and cells. The high expression of MIR4435-2HG is associated with the poor survival rate of patients. The knockout of MIR4435-2HG could repress the proliferation, invasion, migration, and epithelial-mesenchymal transition (EMT), and accelerate the apoptosis of gastric carcinoma cells. Moreover, the deletion of MIR4435-2HG was able to attenuate the tumor growth in vivo. Mechanically, we identified that MIR4435-2HG enhanced Sox4 expression by directly interacting with miR-138-5p as a competitive endogenous RNA (ceRNA) in gastric carcinoma cells, in which Sox4 was targeted by miR-138-5p. Conclusion: MIR4435-2HG is elevated in gastric carcinoma cells, and contributes to the growth, metastasis, and EMT of gastric carcinoma cells by targeting miR-138-5p/Sox4 axis. MIR4435-2HG may be applied as a potential therapeutic target in gastric carcinoma.